Simulium bakalalanense, a new species of the subgenus Gomphostilbia and three new records of black flies (Diptera: Simuliidae) from Mount Murud, Sarawak, Malaysia - Ya'cob, Z.; Takaoka, Hiroyuki; Sofian-Azirun, Mohd (2015)
Simulium (G.) bakalalanense, is described based on male, pupa and larvae collected in Mount Murud, Sarawak, Malaysia. S. (G.) bakalalanense sp. nov. is placed in the S. batoense species-group and is distinguished from most of known species of the group by the pupal gill with an inflated basal fenestra, shoe-shaped cocoon, and lack of grapnel-shaped hooklets on the pupal abdominal segment 9. Three known species, S. (G.) terengganuense Takaoka, Sofian-Azirun & Ya'cob from Peninsular Malaysia, S. (Simulium) alberti Takaoka from Sabah, and S. (S.) beludense Takaoka from Sabah, are newly recorded from Sarawak.